A Lei de Cotas (Lei nº 12.711/2012) e o ingresso nas universidades públicas como mecanismo de política pública antirracista - Almeida, Marcos Antônio Silva de (2022)
Even though Brazil has been moving towards equality among ethnicities, the gap between Afro-Brazilians and whites still remains very high, marked by the presence of racism. This paper initially analyzes racial discrimination in Brazil, from its origins, on different political, economic, and social aspects, including life expectancy, literacy, schooling, occupation, and income. Next, the different conceptions of racism are discussed, namely, the individual, institutional, and structural. Finally, we discussed so-called affirmative action, addressing its origins, characteristics, criticisms and results, especially Law No. 12,711/2012 (Quotas Law) as a form of affirmative action aimed at increasing the access of black and brown people in public institutions of higher education, intending to fulfill the historical debt with the black Brazilian population. Throughout the study, it became apparent that the progress achieved with the public policies implemented so far has not fully translated into income equality: only in 2010 did the income ratio of Afro-Brazilians and whites eclipse its 1960 level, although it seems to be at an all-time high. Education and migration are important factors in the quest to close the gap, while school quality and discrimination may explain its persistence. Therefore, the present study aims to understand the effectiveness of the quota law (Law No. 12,711/2012) regarding the access of blacks in public universities as a mechanism of anti-racist public policy, translating the results obtained as its implementation. It was concluded that racial discrimination can be considered responsible for the existing inequalities between blacks and whites in Brazil, which result from past discrimination, active racial prejudice and stereotypes that legitimize discriminatory attitudes on a daily basis, but that this situation can be changed, either with social mobilization or with the management of state measures of positive discrimination in order to allow black men and women access to positions historically occupied by the white portion. This phenomenon, however, is only feasible because the country is not endowed with a people conscious of the need to revolutionize its constitution, in order to build a new model of society. In light of this, the implementation of anti-racist mechanisms is essential, even if they are merely reformist in nature, in order to meet the current needs of the portion of the black population discriminated against in the country.